2004
DOI: 10.1007/s11661-004-0175-8
|View full text |Cite
|
Sign up to set email alerts
|

The nitriding kinetics of iron-chromium alloys; the role of excess nitrogen: Experiments and modelling

Abstract: To investigate the morphology and the growth kinetics of nitrided layers of Fe-Cr alloys, nitriding experiments were performed for alloys with 4.3, 7.7, 14.0, and 21.5 at. pct Cr. The precipitation morphology of the nitrided samples was investigated with light optical microscopy and scanning electron microscopy (SEM). The elemental compositional variation was determined with electron probe microanalysis. To describe the evolution of the thickness of the nitrided layers, a numerical model was developed that has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 29 publications
1
73
0
Order By: Relevance
“…(i) The (metastable) equilibrium amount of dissolved nitrogen in the ferrite matrix of nitrided iron-based Fe-Al and Fe-Cr alloys can in principle be larger than that for nitrided pure iron, due to (a) a higher nitrogen solubility in iron-based Fe-Al [31] and Fe-Cr alloys [32] as compared to pure iron and (b) the presence of so-called excess nitrogen taken up in the strain fields surrounding the MeN-precipitates. [33][34][35] (ii) Moreover, the development of AlN and CrN precipitates in Fe-Al and Fe-Cr alloys upon nitriding competes with the development of N 2 gas containing pores. Hence, it is concluded from (i) and (ii) that the pore fractions in nitrided Fe-Al and Fe-Cr alloys can be smaller than in nitrided pure iron, as observed (cf.…”
Section: A Pore Formation In Nitrogen Ferrite and The Role Of Alloyimentioning
confidence: 99%
“…(i) The (metastable) equilibrium amount of dissolved nitrogen in the ferrite matrix of nitrided iron-based Fe-Al and Fe-Cr alloys can in principle be larger than that for nitrided pure iron, due to (a) a higher nitrogen solubility in iron-based Fe-Al [31] and Fe-Cr alloys [32] as compared to pure iron and (b) the presence of so-called excess nitrogen taken up in the strain fields surrounding the MeN-precipitates. [33][34][35] (ii) Moreover, the development of AlN and CrN precipitates in Fe-Al and Fe-Cr alloys upon nitriding competes with the development of N 2 gas containing pores. Hence, it is concluded from (i) and (ii) that the pore fractions in nitrided Fe-Al and Fe-Cr alloys can be smaller than in nitrided pure iron, as observed (cf.…”
Section: A Pore Formation In Nitrogen Ferrite and The Role Of Alloyimentioning
confidence: 99%
“…Upon nitriding of iron-based binary alloys containing alloying elements with a strong affinity for nitrogen, such as Cr [10][11][12][13][14][15][16][17][18][19][20][21], Al [22][23][24][25][26][27], V [28][29][30][31][32][33] and…”
Section: Introductionmentioning
confidence: 99%
“…the nitriding potential is sufficiently low [3,4]), (only) a diffusion zone containing chromium-nitride precipitates develops (''internal nitriding''). A number of investigations have been devoted to nitrided iron-chromium alloys [5][6][7][8][9][10][11]. It has been found that the nitriding of Fe-Cr alloys leads to two precipitation morphologies: in the initial stage, fine precipitates with coherent or partly coherent interfaces with the iron matrix develop (so-called ''continuous precipitation'').…”
Section: Introductionmentioning
confidence: 99%
“…more nitrogen than necessary for both (a) precipitation of all chromium as nitride, [N] CrN , and (b) equilibrium saturation of the ferrite matrix, ½N 0 a [6][7][8][9]). It has been suggested that a significant part of the excess nitrogen in nitrided binary iron-based alloys is adsorbed at the nitride/matrix interfaces, [N] interface [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation